2015
DOI: 10.1016/j.ijscr.2015.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel obstruction caused by dried apple

Abstract: HighlightsSmall bowel obstruction in a virgin abdomen can be caused by food bezoar such as rehydrated fruits.Dried apple has a potential to reabsorb fluid and expand up to 35% of its initial size within 72 h.The most common site of small bowel obstruction is proximal to ileocecal valve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The likely underlying mechanism of them causing small bowel obstruction is the high cellulose content as per all phytobezoars with the capability to absorb large quantities of water with subsequent rapid expansion in size and then luminal obstruction of the bowel. 5,6 One experimental study looked at the rate of expansion of dehydrated apple and found they can increase their dehydrated diameter by up to 35%. 6 Diagnosing dehydrated fruit and phytobezoars as a causes of small bowel obstruction is challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The likely underlying mechanism of them causing small bowel obstruction is the high cellulose content as per all phytobezoars with the capability to absorb large quantities of water with subsequent rapid expansion in size and then luminal obstruction of the bowel. 5,6 One experimental study looked at the rate of expansion of dehydrated apple and found they can increase their dehydrated diameter by up to 35%. 6 Diagnosing dehydrated fruit and phytobezoars as a causes of small bowel obstruction is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 One experimental study looked at the rate of expansion of dehydrated apple and found they can increase their dehydrated diameter by up to 35%. 6 Diagnosing dehydrated fruit and phytobezoars as a causes of small bowel obstruction is challenging. Although CT is useful at demonstrating a small bowel obstruction and associated complications, and probable transition points it is poor at specifically demonstrating phytobezoars.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Most of these are managed by surgery after variable periods of conservative treatment. The most common mode of presentation for BLH consists of abdominal pain, particularly "colicky abdominal pain", 11 and nausea and/or vomiting. Listing the full variety of presentations would be extensive, as throughout the literature symptoms such as distended abdomen, constipation, diarrhea, and headaches have all been mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Ingested foreign bodies are particularly rare in adults and can obstruct the intraluminal small bowel. Observed obstructions often include food items, plastics, metals, plants, soil, hair, and insects [1, 2]. Obtaining a comprehension history of a patient's diet as well as clinical imaging renders preoperative diagnosis of ingested foreign bodies possible.…”
Section: Introductionmentioning
confidence: 99%